A topcon solar cell front surface silicon nitride composite film structure inhibiting ultraviolet-induced attenuation and a preparation method thereof

CN123035779APending Publication Date: 2026-11-03CHUZHOU JIETAI NEW ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611327951.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-28
Publication Date
2026-11-03

AI Technical Summary

Technical Problem

Existing TOPCon solar cells suffer from UV-induced degradation (UVID) under ultraviolet light irradiation, which leads to a decrease in cell open-circuit voltage, short-circuit current, and output power. Existing improvement technologies have problems such as high production line modification costs, high costs, or efficiency sacrifices, making them unsuitable for large-scale mass production.

Method used

A six-layer SiNX:H silicon nitride composite film structure is adopted. The ultraviolet transmission light interference destructive interface is formed by the continuous deposition of the bottom layer and the sub-bottom layer. Combined with the low-hydrogen dense silicon nitride film and the silicon-rich high extinction silicon nitride film, ultraviolet light is blocked from entering and hydrogen migration is reduced, thus suppressing the formation of interface defects.

Benefits of technology

It significantly suppresses UV-induced degradation, with power degradation of ≤2.0% after accelerated UV aging at 60kWh/m2. It is compatible with existing production lines without modification, and has low cost without sacrificing battery efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123035779A_ABST
    Figure CN123035779A_ABST
Patent Text Reader

Abstract

The application discloses a TOPCon solar cell front surface silicon nitride composite film structure for inhibiting ultraviolet-induced degradation and a preparation method thereof, and belongs to the technical field of photovoltaic cell manufacturing. X The film layer is a six-layer SiN:H structure, which is sequentially arranged from the side close to the aluminum oxide passivation layer of the cell to the outer side, namely, a bottom layer, a sub-bottom layer, a third layer, a fourth layer, a fifth layer and a top layer; the bottom layer has a refractive index of 1.95+ / -0.02 and a thickness of 10-12 nm; the sub-bottom layer has a refractive index of 2.60-2.70 and a thickness of 10-15 nm; the third layer has a refractive index of 2.30-2.40 and a thickness of 18-25 nm; the fourth layer has a refractive index of 2.10-2.20 and a thickness of 10-15 nm; the fifth layer has a refractive index of 1.98-2.05 and a thickness of 10-15 nm; and the top layer has a refractive index of 1.90-1.98 and a thickness of 8-12 nm; the bottom layer and the sub-bottom layer form an optical matching layer for light interference cancellation in the 280-400 nm wavelength band. The application effectively inhibits UVID through the ultraviolet transmission light interference cancellation and the silicon-rich absorption reduction of the bottom layer and the sub-bottom layer, and the low-hydrogen dense bottom layer blocks the migration of free hydrogen.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of photovoltaic cell manufacturing technology, specifically relating to a silicon nitride composite film structure on the front side of a TOPCon solar cell that suppresses ultraviolet-induced degradation and its preparation method. Background Technology

[0002] N-type TOPCon solar cells employ a boron-diffused p-type emitter paired with an ALD (atomic layer deposition) alumina passivation structure. Alumina achieves excellent surface passivation by fixing negative charges, effectively improving the cell's open-circuit voltage and conversion efficiency. However, the alumina passivation layer is extremely sensitive to ultraviolet light. High-energy ultraviolet light (280-400nm) penetrates the front-side silicon nitride antireflective film, disrupting the Si-H passivation bonds at the Al2O3-silicon substrate interface. This significantly increases the density of interfacial recombination defects, causing a continuous decline in the cell's open-circuit voltage, short-circuit current, and output power. This phenomenon is defined in the industry as ultraviolet-induced degradation (UVID). Current mass-produced TOPCon cells generally use a three-layer silicon nitride antireflective film, which only optimizes antireflection for visible light (400-1100nm) and does not include optical blocking for the ultraviolet band. This results in high ultraviolet light transmittance, and conventional film structures typically exhibit high UV aging degradation, leading to significant power loss in long-term outdoor modules. Existing technologies for improving UVID have significant mass production drawbacks: thickening the alumina passivation layer increases tunneling recombination losses, sacrificing initial cell efficiency; introducing novel functional films such as titanium dioxide and silicon carbide requires new ALD and specialized PECVD (plasma-enhanced chemical vapor deposition) chambers, resulting in high production line upgrade costs; multilayer film segmented deposition processes require multiple vacuum breaking operations, significantly lengthening the coating cycle, reducing capacity, and increasing defect rates; some solutions rely on specialized anti-UV encapsulating adhesives, increasing module encapsulation costs and causing yellowing after long-term use, leading to direct power degradation, thus hindering large-scale mass production and promotion. Currently, the industry lacks an anti-UVID front-side film structure that requires no modification to existing TOPCon mass production workshops, minimally sacrifices cell efficiency, is low-cost, and can be directly introduced into mass production.

[0003] Therefore, there is an urgent need to provide a silicon nitride composite film structure on the front side of TOPCon solar cells that suppresses UV-induced degradation and its preparation method. Summary of the Invention

[0004] The purpose of this invention is to overcome the shortcomings of existing technologies and provide a front-side passivation film and process that combines interface passivation and optical parasitic absorption mechanisms to significantly improve the UVID (ultraviolet-induced degradation) problem. The specific details are as follows: In a first aspect, this application provides a silicon nitride composite film structure for suppressing ultraviolet-induced degradation, wherein the composite film structure is a continuously deposited six-layer SiN XThe :H structure consists of the following layers from the side closest to the aluminum oxide passivation layer of the battery outwards: bottom layer, second bottom layer, third layer, fourth layer, fifth layer, and top layer. The refractive index of the bottom layer is 1.95±0.02, and the thickness is 10~12nm; The sublayer has a refractive index of 2.60~2.70 and a thickness of 10~15nm; The third layer has a refractive index of 2.30~2.40 and a thickness of 18~25nm; The fourth layer has a refractive index of 2.10~2.20 and a thickness of 10~15nm; The fifth layer has a refractive index of 1.98~2.05 and a thickness of 10~15nm; The refractive index of the top layer is 1.90~1.98, and the thickness is 8~12nm; The refractive index difference between the bottom layer and the sub-bottom layer is ≥0.6, and the bottom layer and the sub-bottom layer form an optical matching layer with destructive transmission light interference in the 280~400nm wavelength band.

[0005] Furthermore, the peak ultraviolet extinction coefficient of the sublayer at 280~400nm is 0.32~0.55.

[0006] Furthermore, the bottom layer is a low-hydrogen dense silicon nitride film, and the sub-bottom layer is a silicon-rich high-duration silicon nitride film.

[0007] Furthermore, the hydrogen atom content of the bottom layer is 10-12%; the hydrogen atom content of the sub-bottom layer is 16-18%.

[0008] Secondly, this application provides a TOPCon solar cell based on interference destructive suppression of UVID. The front side of the cell, from the inside to the outside, includes an N-type silicon substrate, a boron-diffused p-type emitter, an ALD aluminum oxide passivation layer, and a silicon nitride composite film structure for suppressing UV-induced degradation as described above.

[0009] Furthermore, the battery is subjected to 60kWh / m 2 After UV accelerated aging, the power attenuation rate is ≤2.0%.

[0010] Thirdly, this application provides a method for fabricating a TOPCon solar cell based on interference destructive suppression of UVID as described above, comprising the following steps: S1. Silicon wafer pretreatment: After texturing, alkaline washing, and acid washing of the silicon wafer in sequence, boron diffusion is performed to prepare the p-type emitter and the borosilicate glass is removed. S2, Front-side aluminum oxide passivation: A 4-6 nm aluminum oxide passivation layer is deposited using the ALD process; S3, PECVD continuous deposition of six layers of silicon nitride composite film: using PECVD equipment, the bottom layer, the second bottom layer, the third layer, the fourth layer, the fifth layer, and the top layer are deposited sequentially on the alumina passivation layer on the front side of the silicon wafer; the deposition of the six layers of silicon nitride composite film is carried out continuously in the same vacuum environment without breaking the vacuum in the middle. S4. Metallization and Sintering: After printing pure silver paste on the front and back sides, high-temperature sintering is carried out to form the electrode structure.

[0011] Furthermore, the deposition temperature in step S3 is 460~520℃.

[0012] Furthermore, in step S3, the refractive index of each layer is controlled only by adjusting the gas flow ratio of SiH4 and NH3 in segments. The SiH4 / NH3 flow ratio of the bottom layer is 1:6 to 1:7, and the SiH4 / NH3 flow ratio of the next bottom layer is 2:1 to 3.5:1.

[0013] Furthermore, the high-temperature sintering temperature in step S4 is 780~820℃.

[0014] This invention, based on the destructive interference of transmitted light and the differentiated design of hydrogen atom content in the film layer, significantly improves the UVID resistance of the front side of the TOPCon battery. Its mechanism of action is as follows: During the ultraviolet incident phase, the transmitted light interference destructively dominates, cutting off the triggering source of high-energy photons. The bottom layer (low-hydrogen dense, n≈1.95) and the sub-bottom layer (silicon-rich high extinction, n≈2.60~2.70) form a high-low refractive index optical matching interface in the 280~400nm ultraviolet band. Through the thin-film transmitted light interference destructive effect, most of the ultraviolet light is reflected back into the air, significantly reducing the total amount of high-energy photons transmitted into the film. At this time, even if there are a certain number of Si-H / NH bonds in the silicon nitride composite film, the source of hydrogen bond breaking is effectively suppressed because the triggering ultraviolet irradiation is greatly weakened, and the release of free hydrogen from hydrogen bond breaking is inhibited at the source. Through the synergistic effect of Fresnel reflection at the high refractive index difference interface and partial interference destructive effect, ultraviolet light is significantly blocked from reaching the alumina passivation layer.

[0015] During the internal evolution of the film, a low-hydrogen dense network dominates, blocking hydrogen migration channels. A small amount of residual ultraviolet light, penetrating the optical interference barrier, enters the underlying layer (the low-hydrogen dense silicon nitride composite film). This layer possesses two key characteristics: first, the low hydrogen atom content means that the number of Si-H / NH bonds available for breakage is extremely limited, naturally restricting hydrogen production under ultraviolet irradiation; second, the dense dielectric network forms a physical barrier layer, making it difficult for even a small amount of free hydrogen generated near the interface to diffuse and migrate across the dense film to the silicon / alumina interface. These two limitations together suppress the free hydrogen concentration at the interface below a safe threshold, preventing the explosive proliferation of hydrogen atoms at the alumina / Si interface that could trigger defect recombination centers, thus ensuring the long-term stability of passivation quality. The two-stage mechanism is sequentially complementary: the optical barrier reduces the ultraviolet injection dose in the early stage, while the low-hydrogen dense film weakens hydrogen production and blocks migration in the later stage. The combination of these two aspects enables the battery to achieve a performance of 60 kWh / m². 2 Even after accelerated UV aging, it maintains excellent anti-aging performance with a power attenuation of ≤2.0%.

[0016] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) This invention utilizes a precise ultraviolet transmittance interference destructive reflection interface formed by the bottom and sub-bottom layers to significantly reduce ultraviolet transmittance in the 280-400nm wavelength range. Simultaneously, the silicon-rich, high extinction properties of the sub-bottom layer strongly absorb residual ultraviolet light, significantly reducing the bombardment of the interface by ultraviolet light. More importantly, the bottom layer employs a low-hydrogen, dense silicon nitride film, which physically blocks ultraviolet light while also acting as a hydrogen migration barrier, effectively suppressing the diffusion of free hydrogen from the top hydrogen-rich layer to the alumina interface and avoiding hydrogen-induced interface defects (such as increased interface state density). This synergistic suppression of UVID through both optical and interfacial chemical pathways enables the battery to achieve a transmittance of 60kWh / m³. 2 Power degradation after aging is ≤2.0%.

[0017] (2) The process is fully compatible with the existing TOPCon production line. Only the PECVD gas ratio program needs to be modified. No new hardware is required, and the production yield remains unaffected. The third layer, a medium-high refractive index transition layer, buffers the film stress and does not peel or crack after damp heat / UV cycling. It also improves the resistance to potential-induced degradation (PID). The encapsulation is compatible with conventional low-cost material systems. No special anti-UV film is required, and the material cost at the module end is not increased. Attached Figure Description

[0018] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0019] Figure 1 This is a comparison curve of the full-spectrum reflectance of Embodiment 1 of the present invention and the baseline scheme; Detailed Implementation To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Therefore, the following detailed description of the embodiments of the present invention is not intended to limit the scope of the claimed invention, but merely to represent selected embodiments of the invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without inventive effort are within the scope of protection of the present invention.

[0020] The present invention will be described in detail below through specific embodiments, and the specific implementation methods are as follows: In a first aspect, the present invention provides a silicon nitride composite film structure for suppressing ultraviolet-induced degradation, wherein the composite film structure is a continuously deposited six-layer SiN X The :H structure consists of the following layers from the side closest to the aluminum oxide passivation layer of the battery outwards: bottom layer, second bottom layer, third layer, fourth layer, fifth layer, and top layer. The refractive index of the bottom layer is 1.95±0.02, and the thickness is 10~12nm; The sublayer has a refractive index of 2.60~2.70 and a thickness of 10~15nm; The third layer has a refractive index of 2.30~2.40 and a thickness of 18~25nm; The fourth layer has a refractive index of 2.10~2.20 and a thickness of 10~15nm; The fifth layer has a refractive index of 1.98~2.05 and a thickness of 10~15nm; The refractive index of the top layer is 1.90~1.98, and the thickness is 8~12nm; The refractive index difference between the bottom layer and the sub-bottom layer is ≥0.6. The bottom layer and the sub-bottom layer form an optical matching layer with destructive transmission light interference in the 280~400nm wavelength band. In addition, the refractive index is the test value at a wavelength of 632nm.

[0021] The bottom layer, immediately adjacent to the alumina passivation layer, is low-hydrogen dense silicon nitride with a refractive index of ~1.95, while the next layer is silicon-rich silicon nitride with a refractive index as high as 2.60~2.70. These two layers form a synergistic structure of sub-quarter-wavelength partial destructive interference and high refractive index difference Fresnel reflection. When ultraviolet light in the 280~400nm band is incident perpendicularly or obliquely, reflected light with opposite phase is generated at the interface between the bottom and the next layer, resulting in destructive interference of transmitted light and significantly weakening the transmitted light energy. Simultaneously, the next layer, employing a silicon-rich stoichiometry, has a significantly increased extinction coefficient in the ultraviolet band, intrinsically absorbing residual transmitted ultraviolet light and converting high-energy photon energy into heat energy for dissipation. Through this combination of "destructive reflection + transmission absorption," most harmful ultraviolet light is blocked at the first and second layer interfaces, preventing it from reaching the Al2O3 / Si sensitive passivation interface.

[0022] Traditional silicon nitride films (especially silicon-rich layers) contain a large number of Si-H and NH bonds. Under ultraviolet light irradiation, high-energy photons easily break the Si-H bonds, releasing free H+. ⁺ / H atoms. These free hydrogen atoms have high mobility and migrate towards the Al2O3 / Si interface along the electric field or concentration gradient, reacting with the interfacial dangling bonds to form recombinations and causing the interfacial state to rise, or directly destroying the substoichiometric coordination structure of Al2O3, which is another important cause of UVID. The bottom layer of this invention is deliberately selected as a silicon nitride thin film with low hydrogen atom content and extremely high density (refractive index 1.95). This layer not only acts as a pre-matching layer for the optical antireflection layer, but also physically acts as a dense hydrogen diffusion barrier layer. It effectively isolates the high-concentration hydrogen source from the third to the top layer from the bottom Al2O3 / Si interface. Even if the upper layer releases free hydrogen during subsequent heat treatment or long-term aging, this dense bottom layer can significantly increase the activation energy of hydrogen migration, preventing it from diffusing to the interface, thereby maintaining the perfect passivation state of the Al2O3 / Si interface.

[0023] As a preferred embodiment, the peak ultraviolet extinction coefficient of the sublayer at 280~400nm is 0.32~0.55.

[0024] As a preferred embodiment, the bottom layer is a low-hydrogen dense silicon nitride film, and the next bottom layer is a silicon-rich high-dust silicon nitride film.

[0025] The low-hydrogen dense silicon nitride film was prepared through the following process: by increasing the deposition temperature, the decomposition reaction of silane and ammonia precursor was promoted, reducing the total amount of residual Si-H and NH bonds in the film; the radio frequency power was increased to enhance ion bombardment densification, the NH3 / SiH4 gas flow ratio was increased and supplemented with N2 dilution, and the chamber pressure was reduced to improve the plasma dissociation degree and distribution uniformity, ultimately obtaining a low-hydrogen-content, dense silicon nitride film. This layer serves as both an optical substrate for ultraviolet interference matching and a physical barrier, preventing the diffusion of free hydrogen released from the upper film during aging to the Al2O3 / Si passivation interface.

[0026] For silicon-rich, high-extinction silicon nitride films, the ultraviolet absorption mechanism is as follows: the optical band gap between the valence band top and conduction band bottom of intrinsic stoichiometric silicon nitride is relatively wide, making it difficult for ultraviolet photons to directly excite interband transitions. When the film is in a silicon-rich state and forms a large number of Si-Si bonds, the Si-Si bond energy level is located inside the Si-N main band gap, which will form extended band tail states at the upper end of the valence band and the lower end of the conduction band, respectively, thus narrowing the material's equivalent optical band gap.

[0027] In the 280–400 nm wavelength range, ultraviolet photon energies (3.1–4.4 eV, 280–400 nm) do not need to reach the intrinsic optical bandgap of the material to excite valence band tail electrons to transition to conduction band tail states. This results in strong ultraviolet absorption through Si-Si bandgap optical transitions, converting high-energy photon energy into heat energy for dissipation. Higher silicon content in the film leads to longer Si-Si bond chains and higher bond density, resulting in greater extension of the bandgap tail states into the deeper bandgap and stronger absorption of ultraviolet light. This further weakens the residual ultraviolet light energy transmitted to the passivation interface.

[0028] In a preferred embodiment, the hydrogen atom content of the bottom layer is 10-12%; the hydrogen atom content of the sub-bottom layer is 16-18%.

[0029] Here, at a deposition temperature of 460~520℃ and a reaction pressure of 160~200Pa, the Si-H bond density in the film can be controlled by adjusting the SiH4 / NH3 flow rate ratio, thereby achieving the aforementioned range of hydrogen atom content.

[0030] Secondly, the present invention provides a TOPCon solar cell based on interference destructive suppression of UVID. The front side of the cell, from the inside to the outside, includes an N-type silicon substrate, a boron-diffused p-type emitter, an ALD aluminum oxide passivation layer, and a silicon nitride composite film structure for suppressing UV-induced degradation as described above.

[0031] As a preferred embodiment, the initial power of the solar cells is tested at a constant temperature, followed by a total UV irradiation of 60 kWh / m². 2 After UV accelerated aging, the power was tested after constant temperature static irradiation, and the power attenuation rate was ≤2.0%.

[0032] Thirdly, the present invention provides a method for fabricating a TOPCon solar cell based on interference destructive suppression of UVID, comprising the following steps: S1. Silicon wafer pretreatment: After texturing, alkaline washing, and acid washing of the silicon wafer in sequence, boron diffusion is performed to prepare the p-type emitter and the borosilicate glass is removed. S2. Frontal aluminum oxide passivation: A 4-6 nm aluminum oxide passivation layer is deposited using ALD process. After deposition, it is annealed for 10-20 min at 400-550℃ in a nitrogen atmosphere to activate the interface and fix the negative charge. S3, PECVD continuous deposition of six layers of silicon nitride composite film: using PECVD equipment, the bottom layer, the second bottom layer, the third layer, the fourth layer, the fifth layer, and the top layer are deposited sequentially on the alumina passivation layer on the front side of the silicon wafer; the deposition of the six layers of silicon nitride composite film is carried out continuously in the same vacuum environment without breaking the vacuum in the middle. S4. Metallization and Sintering: After printing pure silver paste on the front and back sides, high-temperature sintering is carried out to form the electrode structure.

[0033] In a preferred embodiment, the deposition temperature in step S3 is 460~520℃.

[0034] In a preferred embodiment, step S3 only involves adjusting the gas flow ratio of SiH4 and NH3 in segments, combined with constant deposition temperature, pressure and radio frequency power to control the refractive index of each layer. The SiH4 / NH3 flow ratio of the bottom layer is 1:6 to 1:7, and the SiH4 / NH3 flow ratio of the sub-bottom layer is 2:1 to 3.5:1.

[0035] In a preferred embodiment, the high-temperature sintering temperature in step S4 is 780~820℃.

[0036] This invention relates to a TOPCon solar cell based on transmission light interference destructive suppression of UVID. It is a front-side passivation and antireflection film system for TOPCon solar cells. The core of this system utilizes a gradient design of film refractive index and thickness to suppress UV-induced degradation through interference matching in the ultraviolet band, while simultaneously achieving passivation and antireflection performance. The front-side film layers, from the silicon substrate outwards, consist of: an N-type silicon substrate, a boron-diffused p-type emitter, an ALD (aluminum oxide) passivation layer, and six layers of silicon nitride (SiN) continuously deposited via PECVD. X :H) Passivation antireflection film; the six-layer silicon nitride composite film is named sequentially from the alumina passivation layer to the outside: bottom layer, second bottom layer, third layer, fourth layer, fifth layer, and top layer.

[0037] The core design logic of the film system is as follows: the bottom layer and the sub-bottom layer together constitute an interference-matched optical layer in the 280~400nm ultraviolet band. By matching and controlling the refractive index and thickness of the two layers, a reflection enhancement effect is achieved in the ultraviolet band, improving ultraviolet light reflectivity and reducing ultraviolet light transmission into the silicon substrate, thereby mitigating the damage of ultraviolet photons to the cell emitter and passivation layer and suppressing UVID. The nominal refractive index and thickness parameters of the six-layer film are as described above.

[0038] To verify the reflection enhancement effect in the ultraviolet band and analyze the influence of the sub-substructure refractive index configuration on ultraviolet optical performance, two sets of comparison schemes were set up, and the calculation boundary conditions were unified as follows: Core calculation wavelength: 350nm (the core wavelength band for ultraviolet-induced degradation of photovoltaic devices); Incident conditions: perpendicular incidence, ignoring the weak absorption of silicon nitride in the ultraviolet band; Refractive index of the medium: n0=1.0 for incident air and n-Si=3.42 for single-crystal silicon substrate (values ​​in the 300~400nm ultraviolet band). The physical thickness of the film layers is set as follows: 10nm for the top layer (6 layers), the fifth layer, the fourth layer, the second bottom layer, and the bottom layer; and 20nm for the third layer. The film stacking order (from silicon side to the outside) is as follows: silicon substrate, bottom layer, subbottom layer, third layer, fourth layer, fifth layer, top layer; Two comparison schemes were set up: Scheme 1 and Scheme 2. Except for the difference in refractive index between the bottom and sub-bottom layers, the refractive indices of other film layers were taken as fixed representative values, used only for comparative calculations and not representing the optimal values ​​for actual products. The film refractive indices and optical thickness parameters of the two schemes are shown in the table below: Table 1. Refractive index and physical thickness of the film for the two schemes. Based on optical simulation calculations, the reflectance and transmittance of the two schemes in the target ultraviolet band are as follows: Option 1: Reflectivity 17.8%~19.2%, transmittance 80.8%~82.2%; Option 2: Reflectivity 12.4%~13.8%, transmittance 86.2%~87.6%.

[0039] In the 280–400 nm ultraviolet band, the refractive index of the bottom layer in Scheme 1 is 1.95, and the refractive index of the sub-bottom layer is 2.65, with a refractive index difference of 0.70. The abrupt change in refractive index at the interface results in strong Fresnel interface reflection. The physical thickness of the sub-bottom layer is only 10 nm, and its optical thickness is less than a quarter wavelength in this ultraviolet band. The reflected waves from the interfaces of the bottom layer and the sub-bottom layer, as well as the sub-bottom layer and the third layer, partially interfere and cancel each other out. Combined with the strong Fresnel interface reflection caused by the difference in refractive index, the overall film system maintains a high level of ultraviolet reflectance.

[0040] In contrast, Scheme 2 has a bottom layer refractive index of 2.05 and a sub-bottom layer refractive index of 2.35, with a refractive index difference of only 0.30, resulting in a relatively weak interface reflection effect. Scheme 1, through a combination of a high refractive index difference and subwavelength film thickness, achieves an interference-matched reflection enhancement effect in the 280-400nm wavelength range, effectively improving ultraviolet light reflectivity, reducing ultraviolet light transmittance, and decreasing the entry of ultraviolet photons into the silicon substrate, thereby suppressing UVID in TOPCon cells.

[0041] The shorter the wavelength (e.g., 320nm deep ultraviolet band), the more significant the difference in reflectivity between the two schemes. The high refractive index sublayer has a more significant effect on enhancing reflection in the deep ultraviolet band, which can further reduce the deep ultraviolet photons incident on the silicon substrate and more effectively alleviate the ultraviolet-induced degradation of TOPCon cells. Scheme 1, through a larger refractive index gradient differential design, achieves lower transmittance and higher reflectivity across the entire ultraviolet band, which can reduce the irradiation damage of ultraviolet light to the alumina passivation layer and boron emitter. Therefore, it is superior to Scheme 2 in terms of long-term passivation stability and resistance to ultraviolet-induced degradation.

[0042] Example 1 A TOPCon solar cell based on interference destructive suppression of UVID includes the following steps: S1. Silicon Wafer Pretreatment: A 210mm×183mm N-type Czochralski single-crystal silicon wafer with a resistivity of 1.5Ω·cm and a thickness of 130±10μm was selected. Alkali texturing (KOH / ADD system, 80℃, 15min) was performed sequentially to form a pyramidal textured surface. Subsequently, RCA standard cleaning (SC-1 solution + SC-2 solution) was performed to remove surface metallic impurities and organic contaminants. Boron diffusion was carried out using a BCl3 tube diffusion furnace at a diffusion temperature of 930℃, with sheet resistance controlled at 340~420Ω / sq. After diffusion, the back and edge borosilicate glass layers were removed using an HF / HCl mixed acid solution.

[0043] S2. Front-side alumina passivation: An Al2O3 passivation layer was deposited on the front side using an ALD atomic layer deposition system, with trimethylaluminum (TMA) and H2O as precursor sources. The deposition temperature was 200℃, the number of cycles was 30, and the alumina thickness was controlled to 5nm. After deposition, a PECVD process was performed to anneal at 450℃ for 15 minutes in an N2 atmosphere to activate the Al2O3 interface and fix the negative charge.

[0044] S3, PECVD continuous deposition of six layers of silicon nitride composite film: using mass production tubular PECVD equipment, maintaining a vacuum environment (baseline vacuum < 1 × 10⁻⁶) after the silicon wafer is inserted into the chamber. -2The substrate temperature was controlled at 500℃, the RF power at 13.56MHz, and the reaction pressure at 200Pa. The N2 carrier gas flow rate was maintained constant (2000~2500sccm), and continuous six-layer deposition was achieved solely by segmenting the SiH4 to NH3 gas flow ratio, without requiring vacuum breaking per cycle. Bottom layer: SiH4 / NH3 flow ratio adjusted to 1:6.5, depositing low-hydrogen dense SiN with refractive index n=1.95 and a thickness of 11nm. X :H membrane; Subbottom layer: Switch the SiH4 / NH3 flow ratio to 2:1~3:1, and deposit silicon-rich, high-extinction SiN with a refractive index n=2.65 and a thickness of 12nm. X :H membrane; Third layer: Switch the SiH4 / NH3 flow ratio to 1.2:1, deposit a refractive index n=2.35 and a thickness of 22nm; Fourth layer: Switch the SiH4 / NH3 flow ratio to 1:1.2, deposit a refractive index n=2.15 and a thickness of 12nm; Fifth layer: Switch the SiH4 / NH3 flow ratio to 1:2, deposit a refractive index n=2.02 and a thickness of 12nm; Top layer: Switch the SiH4 / NH3 flow ratio to 1:3, deposit a refractive index n=1.94 and a thickness of 10nm.

[0045] The total deposition time for the six layers was approximately 750 seconds. After deposition, the layers were annealed at 300°C for 10 minutes in an NH3 atmosphere.

[0046] Ellipsometry analysis showed that the peak ultraviolet extinction coefficient of the sub-bottom layer at 350 nm was 0.42. Secondary ion mass spectrometry (SIMS) analysis showed that the hydrogen atom content of the bottom layer was 11.2% and that of the sub-bottom layer was 17.1%.

[0047] S4. Metallization and Sintering: Fine grid lines (grid line width 25±2μm) are screen-printed on the front side using pure silver paste, and pure silver grid lines are printed on the back side; then high-temperature sintering is carried out, with the peak temperature controlled at 790℃ and the belt speed at 280 inch / min, to complete the formation of ohmic contacts.

[0048] Example 2 A TOPCon solar cell based on interference destructive suppression of UVID includes the following steps: S1. Silicon Wafer Pretreatment: A 210mm×183mm N-type Czochralski single-crystal silicon wafer with a resistivity of 1.8Ω·cm and a thickness of 130±10μm was selected. Alkali texturing (KOH / ADD system, 80℃, 15min) was performed sequentially to form a pyramidal textured surface structure. Subsequently, RCA standard cleaning (SC-1 solution + SC-2 solution) was performed to remove surface metallic impurities and organic contaminants. Boron diffusion was carried out using a BCl3 tube diffusion furnace at a diffusion temperature of 920℃, with sheet resistance controlled at 340~420Ω / sq. After diffusion, the back and edge borosilicate glass layers were removed using an HF / HNO3 mixed acid solution.

[0049] S2. Front-side alumina passivation: An Al2O3 passivation layer was deposited on the front side using an ALD atomic layer deposition system, with trimethylaluminum (TMA) and H2O as precursor sources. The deposition temperature was 230℃, the number of cycles was 25, and the alumina thickness was controlled to 5nm. After deposition, a PECVD process was performed to anneal at 450℃ for 15 minutes in an N2 atmosphere to activate the Al2O3 interface and fix the negative charge.

[0050] S3, PECVD continuous deposition of six layers of silicon nitride composite film: using mass production tubular PECVD equipment, maintaining a vacuum environment (baseline vacuum < 1 × 10⁻⁶) after the silicon wafer is inserted into the chamber. -2 The substrate temperature was controlled at 500℃, the RF power at 13.56MHz, and the reaction pressure at 160Pa. The N2 carrier gas flow rate was maintained constant (2000~2500sccm), and continuous six-layer deposition was achieved solely by segmenting the SiH4 to NH3 gas flow ratio, without requiring vacuum breaking per cycle. Bottom layer: SiH4 / NH3 flow ratio adjusted to 1:7, depositing low-hydrogen dense SiN with refractive index n=1.95 and a thickness of 11nm. X :H membrane; Subbottom layer: Switch the SiH4 / NH3 flow ratio to 3.5:1, and deposit a silicon-rich, high-extinction SiN with a refractive index n=2.70 and a thickness of 13nm. X :H membrane; Third layer: Switch the SiH4 / NH3 flow ratio to 1.2:1, deposit a refractive index n=2.35 and a thickness of 20nm; Fourth layer: Switch the SiH4 / NH3 flow ratio to 1:1.2, deposit a refractive index n=2.15 and a thickness of 12nm; Fifth layer: Switch the SiH4 / NH3 flow ratio to 1:2, deposit a refractive index n=2.02 and a thickness of 12nm; Top layer: Switch the SiH4 / NH3 flow ratio to 1:3, deposit a refractive index n=1.94 and a thickness of 10nm.

[0051] The total deposition time for the six layers was approximately 760 seconds. After deposition, the layers were annealed at 300°C for 10 minutes in an NH3 atmosphere.

[0052] Ellipsometry analysis showed that the peak ultraviolet extinction coefficient of the sub-bottom layer at 350 nm was 0.35. Secondary ion mass spectrometry (SIMS) analysis showed that the hydrogen atom content of the bottom layer was 10.8% and that of the sub-bottom layer was 16.9%.

[0053] S4. Metallization and Sintering: Fine grid lines (grid line width 25±2μm) are screen-printed on the front side using pure silver paste, and pure silver grid lines are printed on the back side; then high-temperature sintering is carried out, with the peak temperature controlled at 790℃ and the belt speed at 280 inch / min, to complete the formation of ohmic contacts.

[0054] Example 3 A TOPCon solar cell based on interference destructive suppression of UVID includes the following steps: S1. Silicon Wafer Pretreatment: A 210mm×183mm N-type Czochralski single-crystal silicon wafer with a resistivity of 1.5Ω·cm and a thickness of 130±10μm was selected. Alkali texturing (KOH / ADD system, 80℃, 15min) was performed sequentially to form a pyramidal textured surface. Subsequently, RCA standard cleaning (SC-1 solution + SC-2 solution) was performed to remove surface metallic impurities and organic contaminants. Boron diffusion was carried out using a BCl3 tube diffusion furnace at a diffusion temperature of 960℃, with sheet resistance controlled at 340~420Ω / sq. After diffusion, the back and edge borosilicate glass layers were removed using an HF / HCl mixed acid solution.

[0055] S2. Front-side alumina passivation: An Al2O3 passivation layer was deposited on the front side using an ALD atomic layer deposition system, with trimethylaluminum (TMA) and H2O as precursor sources. The deposition temperature was 230℃, the number of cycles was 20, and the alumina thickness was controlled to 4nm. After deposition, a PECVD process was performed to anneal at 550℃ for 15 minutes in an N2 atmosphere to activate the Al2O3 interface and fix the negative charge.

[0056] S3, PECVD continuous deposition of six layers of silicon nitride composite film: using mass production tubular PECVD equipment, maintaining a vacuum environment (baseline vacuum < 1 × 10⁻⁶) after the silicon wafer is inserted into the chamber. -2 The substrate temperature was controlled at 480℃, the RF power at 13.56MHz, and the reaction pressure at 180Pa. The N2 carrier gas flow rate was maintained constant (2000~2500sccm), and continuous six-layer deposition was achieved solely by segmentally adjusting the SiH4 to NH3 gas flow ratio, without requiring vacuum breaking per cycle. Bottom layer: SiH4 / NH3 flow ratio adjusted to 1:6, depositing low-hydrogen dense SiN with refractive index n=1.95 and a thickness of 10nm. X :H membrane; Subbottom layer: Switch the SiH4 / NH3 flow ratio to 2.3:1, and deposit a silicon-rich, high-extinction SiN with a refractive index n=2.65 and a thickness of 10nm. X :H membrane; Third layer: Switch the SiH4 / NH3 flow ratio to 1.4:1, deposit a refractive index n=2.35 and a thickness of 18nm; Fourth layer: Switch the SiH4 / NH3 flow ratio to 1:1.2, deposit a refractive index n=2.15 and a thickness of 10nm; Fifth layer: Switch the SiH4 / NH3 flow ratio to 1:2, deposit a refractive index n=2.02 and a thickness of 10nm; Top layer: Switch the SiH4 / NH3 flow ratio to 1:3, deposit a refractive index n=1.94 and a thickness of 8nm.

[0057] The total deposition time for the six layers was approximately 620 seconds. After deposition, the layers were annealed at 300°C for 10 minutes in an NH3 atmosphere.

[0058] Ellipsometry analysis showed that the peak ultraviolet extinction coefficient of the sub-bottom layer at 350 nm was 0.52; secondary ion mass spectrometry (SIMS) analysis showed that the hydrogen atom content of the bottom layer was 12% and that of the sub-bottom layer was 17.5%.

[0059] S4. Metallization and Sintering: Fine grid lines (grid line width 25±2μm) are screen-printed on the front side using pure silver paste, and pure silver grid lines are printed on the back side; then high-temperature sintering is carried out, with the peak temperature controlled at 780℃ and the belt speed at 280 inch / min, to complete the formation of ohmic contacts.

[0060] Example 4 A TOPCon solar cell based on interference destructive suppression of UVID includes the following steps: S1. Silicon Wafer Pretreatment: A 210mm×183mm N-type Czochralski single-crystal silicon wafer with a resistivity of 1.2Ω·cm and a thickness of 130±10μm was selected. Alkali texturing (KOH / ADD system, 80℃, 15min) was performed sequentially to form a pyramidal textured surface structure. Subsequently, RCA standard cleaning (SC-1 solution + SC-2 solution) was performed to remove surface metallic impurities and organic contaminants. Boron diffusion was carried out using a BCl3 tube diffusion furnace at a diffusion temperature of 930℃, with sheet resistance controlled at 340~420Ω / sq. After diffusion, the back and edge borosilicate glass layers were removed using an HF / HCl mixed acid solution.

[0061] S2. Front-side alumina passivation: An Al2O3 passivation layer was deposited on the front side using an ALD atomic layer deposition system, with trimethylaluminum (TMA) and H2O as precursor sources. The deposition temperature was 250℃, the number of cycles was 30, and the alumina thickness was controlled to 6nm. After deposition, a PECVD process was performed to anneal at 500℃ for 15 minutes in an N2 atmosphere to activate the Al2O3 interface and fix the negative charge.

[0062] S3, PECVD continuous deposition of six layers of silicon nitride composite film: using mass production tubular PECVD equipment, maintaining a vacuum environment (baseline vacuum < 1 × 10⁻⁶) after the silicon wafer is inserted into the chamber. -2 The substrate temperature was controlled at 520℃, the RF power at 13.56MHz, and the reaction pressure at 190Pa. The N2 carrier gas flow rate was maintained constant (2000~2500sccm), and continuous six-layer deposition was achieved solely by segmenting the SiH4 to NH3 gas flow ratio, without requiring vacuum breaking per cycle. Bottom layer: SiH4 / NH3 flow ratio adjusted to 1:6.3, depositing low-hydrogen dense SiN with refractive index n=1.95 and a thickness of 12nm. X :H membrane; Subbottom layer: Switch the SiH4 / NH3 flow ratio to 2.6:1, and deposit silicon-rich, high-extinction SiN with a refractive index n=2.65 and a thickness of 15nm. X :H membrane; Third layer: Switch the SiH4 / NH3 flow ratio to 1.2:1, deposit a refractive index n=2.35 and a thickness of 25nm; Fourth layer: Switch the SiH4 / NH3 flow ratio to 1:1.2, deposit a refractive index n=2.15 and a thickness of 15nm; Fifth layer: Switch the SiH4 / NH3 flow ratio to 1:2, deposit a refractive index n=2.02 and a thickness of 15nm; Top layer: Switch the SiH4 / NH3 flow ratio to 1:3, deposit a refractive index n=1.94 and a thickness of 12nm.

[0063] The total deposition time for the six layers was approximately 880 seconds. After deposition, the layers were annealed at 300°C for 10 minutes in an NH3 atmosphere.

[0064] Ellipsometry analysis showed that the peak ultraviolet extinction coefficient of the sub-bottom layer at 350 nm was 0.39. Secondary ion mass spectrometry (SIMS) analysis showed that the hydrogen atom content of the bottom layer was 11.7% and that of the sub-bottom layer was 17.6%.

[0065] S4. Metallization and Sintering: Fine grid lines (grid line width 25±2μm) are screen-printed on the front side using pure silver paste, and pure silver grid lines are printed on the back side; then high-temperature sintering is carried out, with the peak temperature controlled at 820℃ and the belt speed at 280 inch / min, to complete the formation of ohmic contacts.

[0066] Example 5 A TOPCon solar cell based on interference destructive suppression of UVID includes the following steps: S1. Silicon Wafer Pretreatment: A 210mm×183mm N-type Czochralski single-crystal silicon wafer with a resistivity of 1.4Ω·cm and a thickness of 130±10μm was selected. Alkali texturing (KOH / ADD system, 80℃, 15min) was performed sequentially to form a pyramidal textured surface structure. Subsequently, RCA standard cleaning (SC-1 solution + SC-2 solution) was performed to remove surface metallic impurities and organic contaminants. Boron diffusion was carried out using a BCl3 tube diffusion furnace at a diffusion temperature of 940℃, with sheet resistance controlled at 340~420Ω / sq. After diffusion, the back and edge borosilicate glass layers were removed using an HF / HNO3 mixed acid solution.

[0067] S2. Front-side alumina passivation: An Al2O3 passivation layer was deposited on the front side using an ALD atomic layer deposition system, with trimethylaluminum (TMA) and H2O as precursor sources. The deposition temperature was 250℃, the number of cycles was 25, and the alumina thickness was controlled to 5nm. After deposition, a PECVD process was performed to anneal at 510℃ for 15 minutes in an N2 atmosphere to activate the Al2O3 interface and fix the negative charge.

[0068] S3, PECVD continuous deposition of six layers of silicon nitride composite film: using mass production tubular PECVD equipment, maintaining a vacuum environment (baseline vacuum < 1 × 10⁻⁶) after the silicon wafer is inserted into the chamber. -2 The substrate temperature was controlled at 500℃, the RF power at 13.56MHz, and the reaction pressure at 200Pa. The N2 carrier gas flow rate was maintained constant (2000~2500sccm), and continuous six-layer deposition was achieved solely by segmenting the SiH4 to NH3 gas flow ratio, without requiring vacuum breaking per cycle. Bottom layer: SiH4 / NH3 flow ratio adjusted to 1:6.8, depositing low-hydrogen dense SiN with refractive index n=1.93 and a thickness of 11nm. X :H membrane; Subbottom layer: Switch the SiH4 / NH3 flow ratio to 2.9:1, and deposit a silicon-rich, high-extinction SiN with a refractive index n=2.68 and a thickness of 12nm. X :H membrane; Third layer: Switch the SiH4 / NH3 flow ratio to 1.3:1, deposit a refractive index n=2.38 and a thickness of 23nm; Fourth layer: Switch the SiH4 / NH3 flow ratio to 1:1.1, deposit a refractive index n=2.18 and a thickness of 12nm; Fifth layer: Switch the SiH4 / NH3 flow ratio to 1:1.8, deposit a refractive index n=2.04 and a thickness of 12nm; Top layer: Switch the SiH4 / NH3 flow ratio to 1:2.8, deposit a refractive index n=1.96 and a thickness of 10nm.

[0069] The total deposition time for the six layers was approximately 750 seconds. After deposition, the layers were annealed at 300°C for 10 minutes in an NH3 atmosphere.

[0070] Ellipsometry analysis showed that the peak ultraviolet extinction coefficient of the sub-bottom layer at 350 nm was 0.52. Secondary ion mass spectrometry (SIMS) analysis showed that the hydrogen atom content of the bottom layer was 11.4% and that of the sub-bottom layer was 16.6%.

[0071] S4. Metallization and Sintering: Fine grid lines (grid line width 25±2μm) are screen-printed on the front side using pure silver paste, and pure silver grid lines are printed on the back side; then high-temperature sintering is carried out, with the peak temperature controlled at 800℃ and the belt speed at 280 inch / min, to complete the formation of ohmic contacts.

[0072] Comparative Example 1 A TOPCon solar cell based on interference destructive suppression of UVID is disclosed in this comparative example. The cell is prepared using most of the operation steps in Example 1, except that in step S3, the refractive index of the bottom layer is n=2.10 and the thickness is 11nm; the refractive index of the second bottom layer is n=2.00 and the thickness is 12nm; the third to sixth layers are exactly the same as in Example 1.

[0073] The remaining steps, namely S1 silicon wafer pretreatment, S2 front alumina passivation, and S4 metallization and sintering, are exactly the same as in Example 1.

[0074] Comparative Example 2 A TOPCon solar cell based on interference destructive suppression of UVID is disclosed in this comparative example. The cell is prepared using most of the operation steps in Example 1, except that the refractive index of the sublayer in step S3 is n=2.30 (thickness 12nm), and the other five layers are exactly the same as in Example 1 (bottom layer n=1.95 / 11nm, third layer 2.35 / 22nm, fourth layer 2.15 / 12nm, fifth layer 2.02 / 12nm, top layer 1.94 / 10nm).

[0075] The remaining steps, namely S1 silicon wafer pretreatment, S2 front alumina passivation, and S4 metallization and sintering, are exactly the same as in Example 1.

[0076] Comparative Example 3 A TOPCon solar cell based on interference destructive suppression of UVID is described in this comparative example. The cell is prepared using most of the operation steps in Example 1, except that the thickness of the bottom layer in step S3 is 8 nm (the refractive index is still 1.95), while the thickness and refractive index of the other five layers are exactly the same as in Example 1.

[0077] The remaining steps, namely S1 silicon wafer pretreatment, S2 front alumina passivation, and S4 metallization and sintering, are exactly the same as in Example 1.

[0078] Comparative Example 4 A TOPCon solar cell based on interference destructive suppression of UVID is described in this comparative example. The cell is prepared using most of the operation steps in Example 1, except that the thickness of the bottom layer in step S3 is 4 nm (the refractive index is still 1.95), while the thickness and refractive index of the other five layers are exactly the same as in Example 1.

[0079] The remaining steps, namely S1 silicon wafer pretreatment, S2 front alumina passivation, and S4 metallization and sintering, are exactly the same as in Example 1.

[0080] Comparative Example 5 A TOPCon solar cell based on interference destructive suppression of UVID is described in this comparative example. The cell is prepared using most of the operation steps in Example 1, except that the alumina annealing is omitted in step S2. That is, after deposition, the cell is not annealed at 450°C for 15 minutes in an N2 atmosphere, but directly enters the PECVD process.

[0081] The remaining steps, namely S1 silicon wafer pretreatment, S3, PECVD deposition of front-side silicon nitride antireflection film, and S4 metallization and sintering, are exactly the same as in Example 1.

[0082] Comparative Example 6 A TOPCon solar cell based on interference destructive suppression of UVID is disclosed in this comparative example. The cell is prepared using most of the operation steps in Example 1, except that in step S3, the refractive index of the bottom layer is adjusted to n=2.10, the refractive index of the top layer is adjusted to n=1.8, and the refractive index and thickness of the remaining layers (bottom layer, third layer, fourth layer, and fifth layer) are exactly the same as in Example 1.

[0083] The remaining steps, namely S1 silicon wafer pretreatment, S2 front alumina passivation, and S4 metallization and sintering, are exactly the same as in Example 1.

[0084] Comparative Example 7 A TOPCon solar cell based on interference destructive suppression of UVID is presented in this comparative example. The cell is prepared using most of the operation steps in Example 1, except that: in step S3, the bottom layer is removed, and the remaining five layers are retained. The sublayer is directly exposed to Al2O3, that is, the bottom layer is not deposited, and the sublayer (n=2.65 / 12nm) is directly deposited on Al2O3. Then the third layer (2.35 / 22nm), the fourth layer (2.15 / 12nm), the fifth layer (2.02 / 12nm), and the top layer (1.94 / 10nm) are the same as in Example 1.

[0085] The remaining steps, namely S1 silicon wafer pretreatment, S2 front alumina passivation, and S4 metallization and sintering, are exactly the same as in Example 1.

[0086] Comparative Example 8 A TOPCon solar cell based on interference destructive suppression of UVID is disclosed in this comparative example. The cell is prepared using most of the operation steps in Example 1, except that the refractive index of the third, fourth, fifth and top layers is reduced in step S3, and adjusted to n=2.00 for the third layer, n=1.93 for the fourth layer, n=1.88 for the fifth layer and n=1.83 for the top layer, while the thickness of each layer remains the same as in Example 1.

[0087] The remaining steps, namely S1 silicon wafer pretreatment, S2 front alumina passivation, and S4 metallization and sintering, are exactly the same as in Example 1.

[0088] Comparative Example 9 A TOPCon solar cell based on interference destructive suppression of UVID is disclosed in this comparative example. The cell is fabricated using most of the operational steps described in Example 1, with the difference being that in step S3, the high refractive index layer (n=2.65) is moved from the bottom layer to the fourth layer (near the alumina passivation layer). The film layer order from the inside out is adjusted as follows: bottom layer (n=1.95, 11 nm), third layer (n=2.35, 22 nm), bottom layer (n=2.65, 12 nm), fourth layer (n=2.15, 12 nm), fifth layer (n=2.02, 12 nm), top layer (n=1.94, 10 nm). That is, the high refractive index layer is placed at the bottom of the film system, near the Al2O3 / Si interface, while the thickness of each layer remains consistent with Example 1.

[0089] The remaining steps, namely S1 silicon wafer pretreatment, S2 front alumina passivation, and S4 metallization and sintering, are exactly the same as in Example 1.

[0090] Comparative Example 10 A TOPCon solar cell based on interference destructive suppression of UVID is presented in this comparative example. The cell is fabricated using most of the steps described in Example 1, with the difference being the introduction of SiON in step S3. X and SiO2 layer replaces part of SiN x The layer, film structure is adjusted from the inside out as follows: bottom layer SiN X :H (n=1.95, 11nm), Subbottom layer SiN X :H (n=2.65, 12nm), SiON XLayer (n=1.95, 15nm), SiO2 layer (n=1.46, 12nm); an oxygen-free annealing process (600℃, 20min) is added between steps S2 and S3 to the bottom Al2O3 layer.

[0091] The remaining steps, namely S1 silicon wafer pretreatment, S2 front alumina passivation, and S4 metallization and sintering, are exactly the same as in Example 1.

[0092] Comparative Example 11 A TOPCon solar cell based on interference destructive suppression of UVID is disclosed in this comparative example. The cell is prepared using most of the operation steps in Example 1, except that the refractive index gradient of the third to sixth layers is canceled in step S3. That is, the refractive index gradient of the third layer is n=1.94 / 22nm, the refractive index gradient of the fourth layer is n=1.94 / 12nm, the refractive index gradient of the fifth layer is n=1.94 / 12nm, and the refractive index gradient of the top layer is n=1.94 / 10nm. The refractive index gradient of the bottom layer and the bottom layer are exactly the same as in Example 1.

[0093] The remaining steps, namely S1 silicon wafer pretreatment, S2 front alumina passivation, and S4 metallization and sintering, are exactly the same as in Example 1.

[0094] Comparative Example 12 A TOPCon solar cell based on interference destructive suppression of UVID is presented in this comparative example. The cell is fabricated using most of the operational steps described in Example 1, with the difference being that a low-refractive-index hydrogen transport control layer (SiN2) is inserted between the bottom and subbottom layers in step S3. X H, n=1.95, thickness 5nm. The film structure is adjusted from the inside out as follows: bottom layer (n=1.95, 11nm), hydrogen control layer (n=1.95, 5nm), subbottom layer (n=2.65, 12nm), third layer (n=2.35, 22nm), fourth layer (n=2.15, 12nm), fifth layer (n=2.02, 12nm), top layer (n=1.94, 10nm).

[0095] The remaining steps, namely S1 silicon wafer pretreatment, S2 front alumina passivation, and S4 metallization and sintering, are exactly the same as in Example 1.

[0096] The TOPCon solar cells obtained in Examples 1-5 and Comparative Examples 1-12 were used to make standard solar cell modules, and their performance was tested.

[0097] The method for testing the attenuation rate is as follows: The battery pack was kept at a constant temperature, and its power was tested. The total UV irradiation was 60 kWh / m³. 2 Remove and allow to stand at a constant temperature. Test the power after irradiation. Power attenuation rate = (power before irradiation - power after irradiation) / power before irradiation × 100%.

[0098] In addition, in this document, the refractive index and thickness of the film were measured using an ellipsometer at a wavelength of 632 nm; the hydrogen atom content was determined using secondary ion mass spectrometry (SIMS); and the battery electrical performance parameters were measured under standard test conditions (AM1.5, 1000 W / m). 2 The UV-induced degradation test was performed using an IV analyzer at 25℃; the UV-induced degradation test was conducted using a UV aging test chamber with a total irradiation of 60 kWh / m². 2 .

[0099] The test results of the battery pack performance parameters are shown in Table 2 below.

[0100] Table 2 Performance parameters of battery modules See attached document Figure 1 As shown, Figure 1 The comparison of the full-spectrum reflectance of the optimal embodiment 1 and Bsl (baseline) shows that the short-wavelength response of embodiment 1 is significantly lower than that of Bsl. The battery electrical performance shows that Isc (short-circuit current) decreases and FF increases. This indicates that this part of the incident light did not enter the silicon wafer to generate current, nor was it reflected back into the air by the film layer. Instead, it was continuously reflected in the high and low refractive index film layer, thus losing photon flux.

[0101] This invention achieves a triple anti-UVID mechanism—destructive ultraviolet interference, intrinsic silicon-rich absorption, and hydrogen diffusion blocking—through a core structure of "low-refractive dense sublayer + high-refractive silicon-rich sublayer" combined with a six-layer gradient refractive index silicon nitride film system. The initial power Pmax of Examples 1-5 is concentrated between 617.58 and 618.22 W, and the FF is concentrated between 81.05% and 81.17%, indicating that the six-layer silicon nitride composite film structure of this invention has no significant loss in initial electrical performance, and the consistency among the examples is good. After 60 kWh / m 2 After UV aging, the UV-induced degradation rates of Examples 1-5 were basically controlled between 1.62% and 2.00%, with an average of about 1.81%. Furthermore, the initial power of the conventional three-layer silicon nitride reference scheme was 621.5W, while the initial power of Example 1 of this invention was 618.22W, with an initial efficiency loss of approximately 0.5%, achieving a balance between a significant improvement in UVID resistance and a slight loss in initial efficiency.

[0102] Comparative Examples 1-12 all used Example 1 as the baseline scheme, and modified the film structure, parameters, or process conditions one by one using the controlled variable method. From multiple dimensions such as core mechanism, structural parameters, layer design, process prerequisites, and alternative solutions, the necessity of each design element of the six-layer silicon nitride film system of the present invention was verified in reverse. The ultraviolet power attenuation rate of all comparative examples was significantly higher than that of the Example group (2.78%~3.21% vs 1.62%~2.00%), which fully corroborates the rationality and irreplaceability of the technical solution of the present invention.

[0103] Among them, Comparative Examples 1, 2, and 6 jointly verified that a refractive index difference of ≥0.6 between the bottom layer and the sub-bottom layer is the core threshold for achieving UV interference cancellation and suppressing UVID. Insufficient difference will directly lead to a significant deterioration in UV blocking ability.

[0104] In Comparative Examples 3 and 4, the thickness of the substrate was reduced to 8 nm and 4 nm, respectively (both lower than the 10-12 nm range of this invention), and the attenuation rate increased to 2.90% and 3.00% respectively. The thinner the substrate, the more severe the attenuation, proving that insufficient substrate thickness weakens both the optical interference matching effect and the hydrogen blocking capability. In Comparative Example 7, the substrate was completely removed, allowing the high-fold substrate to directly contact the alumina passivation layer, and the attenuation rate increased to 2.81%, verifying that the dense, low-hydrogen substrate is a key barrier to prevent the diffusion of free hydrogen from the upper layer to the Al2O3 / Si interface and to maintain passivation stability. It is a second anti-attenuation mechanism independent of optical effects. In Comparative Example 12, an additional low-refractive-index layer was inserted between the substrate and the sub-substrate, causing the total thickness of the film adjacent to the alumina passivation layer to exceed the optimal range of 10-12 nm. This disrupted the optical matching effect in the ultraviolet band, leading to a decrease in anti-attenuation performance, verifying that the substrate thickness range defined by this invention is the optimal range that balances optical matching and hydrogen blocking functions. The four sets of comparative examples verified the dual role of the substrate in "optical matching + hydrogen blocking" and the optimal thickness range.

[0105] In Comparative Example 9, the high-refractive-index silicon-rich layer (n=2.65) was moved from the second-to-last layer to the fourth layer, away from the low-refractive-index interface, and the attenuation rate increased to 2.80%. This verifies that the high-refractive-index layer must be close to the low-refractive-index layer to form strong Fresnel reflection and interference matching at the interface; positional deviation will cause the core ultraviolet blocking mechanism to fail, and the anti-attenuation performance will decrease significantly.

[0106] In Comparative Example 8, the overall refractive index of the third to top layers was reduced, weakening the refractive index gradient. The attenuation rate increased to 2.86%, indicating that the upper-layer gradient not only ensures the anti-reflection effect in visible light but also participates in optical matching in the ultraviolet band. In Comparative Example 11, the refractive index gradient of the third to sixth layers was eliminated, unifying them to a low refractive index. The initial power was slightly higher than in Example 1, but the attenuation rate increased to 3.01%, verifying that the gradient structure is key to balancing the initial efficiency and long-term anti-attenuation stability of the battery. Without a gradient, long-term reliability will decrease significantly. The two sets of comparative examples jointly verify the value of the upper four-layer gradient design for performance balance.

[0107] In Comparative Example 5, omitting the annealing activation process for the alumina passivation layer resulted in an attenuation rate of 3.21% (the highest among all samples), indicating that alumina annealing is a necessary process prerequisite for ensuring the basic level of interface passivation and reducing the attenuation substrate. Comparative Example 10 introduced SiON... X The method of replacing part of the silicon nitride with a SiO2 layer and adding an oxygen-free annealing process for alumina resulted in a final attenuation rate of 2.78%, which is still inferior to the performance of the pure silicon nitride six-layer scheme of this invention. Furthermore, it requires additional process steps and consumables, thus demonstrating that the all-silicon nitride scheme of this invention, without any additional processes, has advantages in performance and mass production compatibility. The two sets of comparative examples jointly verify the necessity of the process and the limitations of the alternative schemes.

[0108] In summary, all schemes deviating from the core design of this invention (refractive index difference, layer position, thickness, gradient structure, and process prerequisites) showed significant deterioration in UV-induced degradation. This fully demonstrates that the six-layer film structure and parameter design of this invention are necessary conditions for achieving "low degradation, high efficiency, and high mass production compatibility," and the technical effects have a clear causal relationship. The six-layer SiN of this invention... X The :H front passivation antireflection film structure achieves a good balance between initial efficiency and UVID resistance performance by using the ultraviolet interference cancellation and absorption of the "bottom low-refractive dense layer + the next bottom high-refractive silicon-rich layer", as well as the synergistic effect of the bottom hydrogen barrier and the six-layer refractive index gradient, while being compatible with the existing PECVD mass production process.

[0109] The present invention has been further described above with reference to specific embodiments. However, it should be understood that the specific description herein should not be construed as limiting the nature and scope of the present invention. Various modifications made to the above embodiments by those skilled in the art after reading this specification are all within the scope of protection of the present invention.

Claims

1. A silicon nitride composite film structure for suppressing UV-induced degradation, characterized in that, The composite film structure is a continuously deposited six-layer SiN X The :H structure consists of the following layers from the side closest to the aluminum oxide passivation layer of the battery outwards: bottom layer, second bottom layer, third layer, fourth layer, fifth layer, and top layer. The refractive index of the bottom layer is 1.95±0.02, and the thickness is 10~12nm; The sublayer has a refractive index of 2.60~2.70 and a thickness of 10~15nm; The third layer has a refractive index of 2.30~2.40 and a thickness of 18~25nm; The fourth layer has a refractive index of 2.10~2.20 and a thickness of 10~15nm; The fifth layer has a refractive index of 1.98~2.05 and a thickness of 10~15nm; The refractive index of the top layer is 1.90~1.98, and the thickness is 8~12nm; The refractive index difference between the bottom layer and the sublayer is ≥ 0.6, the bottom layer and the sub-bottom layer form an optical matching layer with destructive transmission light interference in the 280~400nm wavelength band.

2. The silicon nitride composite film structure for suppressing UV-induced degradation according to claim 1, characterized in that, The peak ultraviolet extinction coefficient of the sublayer at 280~400nm is 0.32~0.

55.

3. The silicon nitride composite film structure for suppressing UV-induced degradation according to claim 1, characterized in that, The bottom layer is a low-hydrogen dense silicon nitride film, and the sub-bottom layer is a silicon-rich high-dust silicon nitride film.

4. The silicon nitride composite film structure for suppressing UV-induced degradation according to claim 3, characterized in that, The hydrogen atom content of the bottom layer is 10-12%; the hydrogen atom content of the sub-bottom layer is 16-18%.

5. A TOPCon solar cell based on interference destructive suppression of UVID, characterized in that, The front side of the battery, from the inside to the outside, includes an N-type silicon substrate, a boron-diffused p-type emitter, an ALD aluminum oxide passivation layer, and a silicon nitride composite film structure for suppressing UV-induced degradation as described in any one of claims 1-4.

6. The TOPCon solar cell based on interference destructive suppression of UVID according to claim 5, characterized in that, The battery is rated at 60kWh / m 2 After UV accelerated aging, the power attenuation rate is ≤2.0%.

7. A method for fabricating a TOPCon solar cell based on interference destructive suppression of UVID according to claim 5 or 6, characterized in that, Includes the following steps: S1. Silicon wafer pretreatment: After texturing, alkaline washing, and acid washing of the silicon wafer in sequence, boron diffusion is performed to prepare the p-type emitter and the borosilicate glass is removed. S2, Front-side aluminum oxide passivation: A 4-6 nm aluminum oxide passivation layer is deposited using the ALD process; S3, PECVD continuous deposition of six layers of silicon nitride composite film: using PECVD equipment, the bottom layer, the second bottom layer, the third layer, the fourth layer, the fifth layer, and the top layer are deposited sequentially on the alumina passivation layer on the front side of the silicon wafer; The deposition of the six-layer silicon nitride composite film was carried out continuously in the same vacuum environment without breaking the vacuum. S4. Metallization and Sintering: After printing pure silver paste on the front and back sides, high-temperature sintering is carried out to form the electrode structure.

8. The method for fabricating a TOPCon solar cell based on interference destructive suppression of UVID according to claim 7, characterized in that, The deposition temperature in step S3 is 460~520℃.

9. The method for fabricating a TOPCon solar cell based on interference destructive suppression of UVID according to claim 7, characterized in that, In step S3, the refractive index of each layer is controlled by adjusting the gas flow ratio of SiH4 and NH3 in segments. The SiH4 / NH3 flow ratio of the bottom layer is 1:6 to 1:7, and the SiH4 / NH3 flow ratio of the next bottom layer is 2:1 to 3.5:

1.

10. The method for fabricating a TOPCon solar cell based on interference destructive suppression of UVID according to claim 7, characterized in that, The high-temperature sintering temperature in step S4 is 780~820℃.